2013
DOI: 10.1017/s1092852913000795
|View full text |Cite
|
Sign up to set email alerts
|

Hypochondriasis and obsessive-compulsive disorder in schizophrenic patients treated with clozapine vs other atypical antipsychotics

Abstract: Hypochondriasis could represent an important clinical feature of schizophrenic patients treated with atypical antipsychotics, and further research is needed in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…Patients with schizophrenia treated with clozapine reported having a higher prevalence of hypochondriasis and OC spectrum of illnesses, and a part of this was attributed to the de novo onset or an exacerbation of existing symptoms 7. Worsening of existing symptoms occurs in a subgroup of patients with hypochondriasis/OCD, who had certain polymorphisms of SLC1A1/GRIN2B genes, whereas the de novo occurrence of OC symptoms was attributed to the role of clozapine’s strong antagonistic activities at 5-HT2A, 5-HT1C, 5-HT2C and glutamatergic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with schizophrenia treated with clozapine reported having a higher prevalence of hypochondriasis and OC spectrum of illnesses, and a part of this was attributed to the de novo onset or an exacerbation of existing symptoms 7. Worsening of existing symptoms occurs in a subgroup of patients with hypochondriasis/OCD, who had certain polymorphisms of SLC1A1/GRIN2B genes, whereas the de novo occurrence of OC symptoms was attributed to the role of clozapine’s strong antagonistic activities at 5-HT2A, 5-HT1C, 5-HT2C and glutamatergic receptors.…”
Section: Discussionmentioning
confidence: 99%
“…As it can be understood from these similar findings, it is seen that OCD and hypochondriasis may share similar etiopathogenetic resources, and in this context, it is useful to recall previous articles on thyroid functions in OCD patients [ 3 , 8 10 ].…”
Section: Highlight Key Pointsmentioning
confidence: 98%
“…A recent study showed that also hypochondriasis (HYPO) is more frequent in patients with SCH (20%) than in the general population (1%) and that its prevalence is higher in patients treated with CLZ (36.7%) than in those treated with other antipsychotics (6.7%) [4]. …”
Section: Introductionmentioning
confidence: 99%